Voluntary Carbon Markets: A Review on Efficacy, Challenges and Impacts on Corporate Emissions Reductions Targets - Manner, Ida (2024)
The escalating threat of global warming has prompted many developed economies to implement carbon emission reduction policies to meet the Paris Agreement's 1.5°C target. However, current global climate pledges remain insufficient, necessitating urgent additional measures for emissions reductions and removals. In response, governments and international organizations are increasingly relying on non-state actors to help bridge this gap, with voluntary carbon offsetting emerging as a key tool for corporations to reduce their greenhouse gas emissions. Initially conceived as a supplementary climate action measure, voluntary carbon offsets have gained popularity as companies seek to appeal to climate-conscious consumers and enhance their environmental performance. Despite their potential, voluntary offsetting initiatives have faced significant criticism due to concerns about transparency, credibility, and the risk of greenwashing. The debate over the credibility of carbon offsetting as a solution to climate change includes concerns that corporations might use offsets to make misleading claims about their environmental impact. As the use of voluntary offsets continues to grow, it is crucial to address these challenges to ensure that offsetting activities genuinely contribute to global climate change mitigation efforts. This Master’s Thesis approaches the topic by conducting a comprehensive review of the existing literature on voluntary carbon offsets, analyzing studies focused on corporate offsetting practices, and evaluating the effectiveness of these practices in achieving real emission reductions. Furthermore, this thesis explores the regulatory frameworks governing voluntary carbon markets and assesses the potential for reforms to enhance transparency and accountability. By synthesizing the findings, the thesis aims to provide insights into how voluntary carbon offsets can be improved to serve as a more credible and effective tool in global climate change mitigation.